Aprendizagem histórica e história local: uma experiência com alunos do 8º ano sobre o ensino da História de Parauapebas-PA - Leite, Mayara Alves (Universidade Federal do Tocantins, 2020)
The present study aimed to investigate how students' historical learning occurs from the use of local history. We present some reflections regarding the prescription of teaching local history in educational curricula at national, state and municipal levels. The research is of a qualitative nature. The methodology used is oral history. This research method was chosen with the intention of understanding and reflecting on the existing narratives around its emergence. We hypothesized that teaching local history can be an important tool for the development of students' historical learning, because by reflecting on the present, past and future, they will be able to think of its importance as a historical subject, understanding themselves with a substantial part for the construction community and the strengthening of its local identity, and perceiving itself as a transforming agent for its group. To respond to the suggested hypothesis, stages were organized with different interventions: questionnaires with open questions related to the teaching of history and local history, analysis of poems about the municipality, text on local history, workshop with interview techniques and interviews with two people who reside in Parauapebas from the period prior to emancipation to the present day. As a pedagogical didactic product, we developed a flexible planning proposal, with guidelines on the methodologies used in our research that proved to be effective, to be applied by teachers according to their reality.